Influential Article Review - Producing Content for Everybody - Mendoza, Sue; Johnson, Sharon; Figueroa, Harriet (Journal of Marketing Development and Competitiveness, 2019)
This paper examines technology and art. We present insights from a highly influential paper. Here are the highlights from this paper: : Generative art is created by a system that operates autonomously, or semi-autonomously, rather than directly by the artist. The artist creates the system and establishes parameters that affect the outcome, but the outcome itself emerges from the system rather than from the artist. Generative art systems are frequently computer programs, although biological, social, or other systems may also be used as well. Computer programming environments are often technically demanding, but there are also those that are more accessible and offer novices ways to engage with concepts and practices of generative art. We report on our experience with two such environments, TurtleArt and Scratch, that we have used in workshops with preservice and in-service teachers over the past several years. TurtleArt and Scratch are two programming environments that are accessible to novices and provide a way to explore and create works of generative art. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.